COMPARISON OF EFFICACY OF INJECTABLE STEROIDS VERSUS CONSERVATIVE MANAGEMENT FOR DE QUERVAINS’S TENOSYNOVITIS - Nasim Ilyas; Fouzia Hanif; Rajesh Kumar Panjwani; Sheikh Kashif Rahim; Asma Abdul Qadeer; Abdul Hameed (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: De Quervain's tenosynovitis is tenosynovitis of the abductor pollicis longus and extensor pollicis brevis tendons, occurs due to chronic overuse of the wrist and hand. To compare effectiveness of steroid injection with conservative management of De Quervains’s tenosynovitis.METHODOLOGY: Randomized prospective study was conducted at the various private orthopedic clinic across Rawalpindi district, along with collaboration of community medicine department, Rawal Institute of health sciences, Islamabad. The study population was divided into two groups, i.e., group A and group B. Group A was given inj. corticosteroid and group B was given conservative management. The severity of pain (Visual analogue scale) and Finkelstein test were recorded on baseline and after 3 weeks follow up.RESULTS: Our study included 96 diagnosed cases of de Quervains tenosynovitis on a positive Finkelstein test; 48 were given corticosteroid injection and 48 were conservatively treated. The mean age in corticosteroid’s injection group was 34.76+6.95 years whereas the mean age in conservative management group was 31.7+8.91 years. Post-intervention 13, 29 patients had a positive Finkelstein test in corticosteroid and conservative groups respectively. Although the difference in pre intervention pain score between the two groups was not statistically significant but significantly lesser pain scores in the corticosteroid group; (p= 0.00).CONCLUSION: Steroid injection produced better results in terms of relief in pain and negative Finkelstein test as compared to conservative treatment.